PERANCANGAN MASKOT PRODUK BOWAH (BOBA BUWAH NAGA) - Raia, Divanna Hikary (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
In the business world, branding and brand identity are important keys to creating a positive impression on consumers and increasing the competitiveness of local products in the global market. This journal discusses the process of designing the mascot